2016
DOI: 10.1371/journal.pone.0167912
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organizing Global Gene Expression Regulated through Criticality: Mechanism of the Cell-Fate Change

Abstract: BackgroundA fundamental issue in bioscience is to understand the mechanism that underlies the dynamic control of genome-wide expression through the complex temporal-spatial self-organization of the genome to regulate the change in cell fate. We address this issue by elucidating a physically motivated mechanism of self-organization.Principal FindingsBuilding upon transcriptome experimental data for seven distinct cell fates, including early embryonic development, we demonstrate that self-organized criticality (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
129
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(153 citation statements)
references
References 84 publications
21
129
0
Order By: Relevance
“…A complete erasure of the zygote state's criticality occurs after the late 2-cell state, such that a critical transition state should exist right after the late 2-cell state. Recently, we demonstrated that essentially the same critical-state dynamics that we observed for cell differentiation processes [4,6] are also present in overall RNA expression in Figure 7). Sandpile-type critical behaviors, which exhibit diverging up-and down-regulation at a critical point (CP: ln<nrmsf>~− 5.5), emerge in overall expression sorted and grouped according to the fold-change in expression (see stochastic resonance in [6]).…”
Section: -Cell(m)supporting
confidence: 76%
See 4 more Smart Citations
“…A complete erasure of the zygote state's criticality occurs after the late 2-cell state, such that a critical transition state should exist right after the late 2-cell state. Recently, we demonstrated that essentially the same critical-state dynamics that we observed for cell differentiation processes [4,6] are also present in overall RNA expression in Figure 7). Sandpile-type critical behaviors, which exhibit diverging up-and down-regulation at a critical point (CP: ln<nrmsf>~− 5.5), emerge in overall expression sorted and grouped according to the fold-change in expression (see stochastic resonance in [6]).…”
Section: -Cell(m)supporting
confidence: 76%
“…Recently, we demonstrated that essentially the same critical-state dynamics that we observed for cell differentiation processes [4,6] are also present in overall RNA expression in single-cell mouse embryo development, which presents further proof of SOC control as a universal characteristic [13]. Overall RNA expression and its dynamics exhibit typical features (genome avalanche and sandpile type criticality) of self-organized criticality (SOC) control in mouse embryo development; Figure 1 shows a genome avalanche, i.e., scaling-divergent behavior in a log-log-scale plot between expression and the temporal variance of expression (nrmsf ).…”
Section: -Cell(m)supporting
confidence: 73%
See 3 more Smart Citations